P48 The effects of tgf-Β and il-33 on the pro-fibrotic activity of primary human lung fibroblasts during the development of ipf. (15th November 2017) - Stephenson, KE; Overed-Sayer, CL; John, AE; Cohen, ES; Jenkins, RG
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a debilitating interstitial lung disease with a poor prognosis and limited treatment options. It is a chronic, progressive, condition characterised by the excessive deposition of extracellular matrix by fibroblasts. Transforming growth factor-β (TGF- β) is central to this process and is regarded as a key pro-fibrotic mediator in IPF. Recently, emerging evidence suggests that the cytokine interleukin-33 (IL-33) may also be important in the development of IPF. However, the cellular and molecular mechanisms by which IL-33 promotes fibrosis are unknown. In particular, whether TGF-β and IL-33 have independent pro-fibrotic effects on fibroblasts remains unclear. Methods: Primary human lung fibroblasts (HLFs) from non-IPF and IPF patients were treated with either 2 ng/ml TGF-β or 10 ng/ml IL-33. The levels of IL6 and IL8 mRNA were used as readouts of IL-33-mediated NF-κβ activation whilst ACTA2 and COL1A1 mRNA were used as readouts of fibrosis. mRNA levels were measured by real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR). Finally, the levels of IL-33, and its receptor ST2, were measured by qRT-PCR to assess mRNA expression and western blotting to measure protein. Results: Stimulation with TGF-β for 8 hours induced statistically significant increases in IL33 gene expression by both non-IPF and IPF HLFs. Moreover, TGF-β stimulation of HLFs from patients with and without IPF induced IL-33 protein as assessed by immunoblotting. To assess the functional consequence of TGF-b induced IL-33 from fibroblasts, the effect of recombinant IL-33 on HLFs was determined. Increasing concentrations of IL-33 failed to stimulate IL6, IL8, ACTA2 and COL1A1 gene expression by either IPF or non-IPF fibroblasts. To understand the lack of IL-33 responsiveness in HLFs, ST2 levels were measured and neither ST2 mRNA or protein were detectable in IPF, or non-IPF, HLFs. Conclusion: TGF-β increases IL-33 production by HLFs, however fibroblast-derived IL-33 does not act directly on fibrotic fibroblasts as they fail to express the receptor required for IL-33 responsiveness. Therefore, the pro-fibrotic effects of IL-33 are likely mediated via alternative cell types.